Rural priests in early 20th century: experience of solving economic problems of flock for current conditions - Fareniy, I. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. Among the topics that have become the subject of scientific studies of the modern historiography is participation of the priesthood in solving social problems, including economic ones. The paper submitted proposes proceeding on this topic. The need for further study is caused by the opportunity to deepen the knowledge about participation of the clergy in social life. The goal of the paper is to broaden scientific understanding about background and essence of activity of rural clergy in Ukrainian governorates of the Russian Empire in the field of economic modernization of peasantry and to show real potential of religious ideology and priests in social and economic problem solving. Results. Participation of priests in solving economic problems of their flock was caused by general European trends of religious development. In the 19th – early 20th centuries the clergy had an intention to build a social order that would meet Christian standards of social relations. In the Russian Empire such approach was followed by some Orthodox priests, leading to their try to build a socio-economic system that would meet the teachings of Christ. Economic people-oriented activity of rural clergy involved activities on agricultural update and cooperation promotion. During public worship, study at parochial schools and in daily communication the priesthood taught rural people the latest agricultural achievements, distributed relevant literature, helped with creation and operation of cooperative associations. Among intelligentsia Orthodox clergy was one of the most active organizers and leaders of cooperative movement. There were experienced, competent and well known cooperators among them. Originality. The paper broadens understanding about background and essence of activity of rural clergy in Ukrainian governorates of the Russian Empire in the field of economic modernization of peasantry and shows real potential of religious ideology in this field. Conclusions. Participation of the priesthood in socio-economic problem solving was a broad social movement of the clergy to implement religious values into real life. The clergy showed a high capacity for practical organizational and economic work in favour of Ukrainian peasantry. Experience of the early 20th century teaches that in the current context social potential of priests should be aimed at normalization of economic life in the countryside.